Ethnobotanical Study of Sasak Traditional House At Ende Village, Central Lombok Regency, West Nusa Tenggara - Silva, Baiq Regina; Sukenti, Kurniasih; Sukiman, Sukiman (Metamorfosa: Journal of Biological Sciences; Vol 10 No 2 (2023)DO - 10.24843/metamorfosa.2023.v10.i02.p18, 2023)
Sasak traditional houses at Ende Village, Central Lombok Regency still use plants as constituents. Local wisdom and social culture related to Sasak traditional houses are still maintained. This study aims to document the ethnobotanical knowledge of the community related to the Sasak traditional house. This exploratory descriptive research was carried out through qualitative and quantitative approaches based on data collection including observation, interviews, documentation, and identification. The sampling technique was using purposive sampling and snowball sampling methods. Qualitative data were analyzed descriptively and quantitative data through calculations free listing , Cultural Significance Index (CSI), and Fidelity Level (FL). There are 18 species of plants from 6 families that are used for traditional Sasak houses and 12 kinds of plant utilization including roofs, poles, buffers, doors, walls, fences, floors, storage of goods, stairs, unifiers, pedestal of sit, and others. CSI value of Swietenia macrophylla Raja. sebagai spesies dengan nilai kepentingan tertinggi 41,25 untuk 7 jenis pemanfaatan dan lebih direkomendasikan untuk digunakan sebagai tiang sehingga diperoleh nilai FL sebesar 100%. Upaya konservasi dilakukan dengan menanam kembali jenis tumbuhan untuk material rumah adat Sasak. Sosial budaya dan kearifan lokal terkait rumah adat Sasak diterapkan melalui pemanfaatan jenis tumbuhan dalam proses pembangunan rumah adat Sasak. Penelitian ini diharapkan dapat menjaga konsistensi pengetahuan masyarakat tentang pentingnya melestarikan sumber daya alam dan kearifan lokal bagi rumah adat Sasak di masa mendatang.